1970
DOI: 10.1111/j.1478-4408.1970.tb02918.x
|View full text |Cite
|
Sign up to set email alerts
|

Photodegradation of Cotton Cellulose

Abstract: The relation between the fading and phototendering behaviour of Caledon Yellow GN, 5GK and 4G on cotton cellulose has been examined. A distinction is drawn between the reactions promoted by visible light and those promoted by ultraviolet radiation. Caledon Yellow 5GK is the most efficient phototenderer in visible light and production of the leuco dye accompanies this process. Phototendering by this mechanism can also be identified with Caledon Yellow GN, although to a much smaller extent than with 5GK, and pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1970
1970
1996
1996

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…The phototropic behaviour of flavanthrone, which has been known for many years, has recently been studied extensively by Feichtmayr and Schlag (22) and by Fiebig (23). Their spectral results show that on irradiation the yellow dye is reduced to the green acid leuco form (AH2) of the dye (A), and not to the blue ionised alkaline leuco form (A2-) as appears to be suggested by Baugh et al (24). In the latter paper the use of the wavenumber scale as abscissa for the reflectance curves of flavanthrone in its reduced and oxidised states makes comparison with the spectrum of the irradiated dyeing inexact, since the interesting spectral changes are in the longer wavelength region, but the work reported by Fiebig (23) illustrates the clear and substantial difference of leuco flavanthrone in the alkaline and acid states.…”
Section: Spectral Changes In Vat-dyed Polymer Filmsmentioning
confidence: 78%
See 1 more Smart Citation
“…The phototropic behaviour of flavanthrone, which has been known for many years, has recently been studied extensively by Feichtmayr and Schlag (22) and by Fiebig (23). Their spectral results show that on irradiation the yellow dye is reduced to the green acid leuco form (AH2) of the dye (A), and not to the blue ionised alkaline leuco form (A2-) as appears to be suggested by Baugh et al (24). In the latter paper the use of the wavenumber scale as abscissa for the reflectance curves of flavanthrone in its reduced and oxidised states makes comparison with the spectrum of the irradiated dyeing inexact, since the interesting spectral changes are in the longer wavelength region, but the work reported by Fiebig (23) illustrates the clear and substantial difference of leuco flavanthrone in the alkaline and acid states.…”
Section: Spectral Changes In Vat-dyed Polymer Filmsmentioning
confidence: 78%
“…Baugh e t al. (24), from a consideration of the behaviour of three vat dyes, found that the dye that promoted the greatest degradation with visible radiation was the most efficient desensitiser to short-wave ultraviolet radiation. On the basis of this finding, they suggested two competing processes for the degradation of the cellulose: (a) direct transfer of electronic energy from the excited dye system to the cellulose, which would lead to efficient degradation, as in direct photolysis in the undyed state, and (b) absorption of 253.7-nm radiation by the vat dye, leading to internal conversion from the X X * state to the n~* state allowing the latter state to participate in hydrogenabstraction reactions.…”
Section: Action Of Short-wave Ultraviolet Radiation On Dyed Cellulosementioning
confidence: 99%